Tổng hợp vật liệu bằng phương pháp phản ứng nổ và tính chất của LaPO4:Eu kích thước nanomet - Vũ, Nguyễn; Roãn, Phạm Đức; Thắng, Tạ Minh; Kim Chi, Trần Thị; Nam, Mẫn Hoài; Thanh, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
Eu (III) -doped LaPO4 nanophosphors were prepared via combustion synthesis using urea as fuel and metal nitrates as precursor. Structures, morphologies, and photoluminescent properties of the LaPO4:Eu were studied by X-ray diffraction, scanning electron microscopy, photoluminescent and excitation photoluminescent spectra. The average diameters for the phosphor particles are 5-20 nm. The effects of Eu(III) doping process and heating temperature on structure and optical properties of nanophosphors have been investigated. LaPO4:Eu phosphors show the intense peak at 594 nm corresponding to the 5D0-7F1 transition of Eu (III) in inversion symmetry sites.